ARAHAN PELESTARIAN TATA RUANG PERMUKIMAN MASYARAKAT ETNIS MANDAILING DI SUMATERA UTARA - Cut Nuraini; Qaanitah Azizah; Sri Muharrani (Universitas Muhammadiyah Jakarta, 2024)
The Mandailing community settlement in North Sumatra has many historic elements. The purpose of this research is to identify the physical and non-physical aspects of the Mandailing community's residential areas in three villages that have the potential to be preserved and maintained, as well as to determine how large an area is appropriate for conservation. This study employs a descriptive-exploratory-qualitative approach to identify settlement physical elements (buildings, open spaces, and roads) and non-physical elements (socio-cultural, layout, orientation, and patterns) with the potential to be preserved. According to the study, physical characteristics are classified into physical buildings and non-buildings. Bagas Godang, Sopo Godang, Sopo Emme, mosques, Pancur Paridian, Sopo Saba, Sopo Ladang, and Bale Hombung are among the physical elements of the structure. Alaman Bolak Selangseutang, roads, rivers, plantation areas, fields, rice fields, and forests are non-building physical features. Non-physical aspects that impact the settlement environment include: a) using the Banua principle, b) differences in village status, and c) the spatial Dalihan Natolu Social System. Overall, the Mandailing residential area can be divided into two zones: conservation areas, which are planned to be renovated, restored, and rehabilitated using contextual Mandailing architectural designs while still adhering to local regulations, and preservation areas, which are allowed to preserve the existence of each of its constituent elements while adhering to local laws. The preservation and conservation policies that will be implemented in each case will be handled in a specific order based on established criteria, namely immediate handling of case 4 and subsequent handling of the following three points in the order of handling case 2, case 3, and case 1. Salah satu kawasan di Indonesia yang memiliki banyak elemen-elemen bersejarah adalah permukiman masyarakat Mandailing di Sumatera Utara. Kajian ini bertujuan untuk mengidentifikasi elemen-elemen fisik dan non fisik kawasan permukiman masyarakat Mandailing di tiga kampung yang berpotensi untuk dilestarikan dan dipertahankan keberadaannya serta menentukan seberapa luas kawasan yang layak untuk di konservasi. Kajian ini menggunakan metode deskriptif-eksploratif-kualitatif yang berupaya mengidentifikasi elemen fisik permukiman (bangunan, ruang terbuka, jalan) dan elemen non-fisik (sosial-budaya, tata letak, orientasi, pola) yang potensial untuk dilestarikan. Hasil penelitian menunjukkan aspek-aspek non-fisik yang dapat dilihat pengaruhnya terhadap lingkungan permukiman ini antara lain adalah a) penerapan prinsip Banua; b) perbedaan status kampung; c) Sistem Sosial Dalihan Natolu yang me-ruang. Secara keseluruhan kawasan permukiman Mandailing ini dapat diklasifikasikan atas dua kategori zona yaitu pertama, kawasan konservasi yang direncanakan untuk direnovasi, direstorasi dan direhabilitasi melalui kontekstual desain arsitektur Mandailing dan tetap memperhatikan aturan-aturan setempat; dan kedua, kawasan preservasi yang diberi kesempatan untuk tetap mempertahankan keberadaan tiap elemen-elemen penyusunannya tetapi juga tetap mempertahankan aturan-aturan setempat. Urutan penanganan terhadap kebijakan preservasi dan konservasi yang akan dilakukan pada tiap kasus memiliki urutan tertentu berdasar kriteria yang ditetapkan, yaitu penanganan segera terhadap kasus 4 dan penanganan berikutnya pada tiga kasus berikutnya dengan urutan penanganan adalah kasus 2, kasus 3 dan kasus 1.